PENGARUH DISPOSISI MATEMATIS TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS XI IPS MAN 1 KOTA PADANG - Utami, Selvina Riska Putri (Departemen Matematika, 2023)
This study is to determine the effect of mathematical disposition on mathematical communication skills of students in class XI IPS MAN 1 Padang City. The type of research used is ex-post facto research. The population in this study were students of class XI social studies MAN 1 Padang City in the academic year 2023/2024 totaling 72 students. The instruments used in this study were mathematical disposition questionnaire and mathematical communication ability test. Data were analyzed with descriptive statistics and inferential statistical analysis with simple linear regression. Based on the results of descriptive analysis, it is known that most students have poor mathematical ability. Regarding students' mathematical communication skills, the results obtained were 19.44% in the